KEMAMPUAN BERPIKIR KRITIS MAHASISWA DI PROGRAM STUDI PENDIDIKAN AKUNTANSI - Purba Andy Wijaya; Fitriani (UIR Press, 2021)
The purpose of this study was to determine the critical thinking skills of students in the Accounting Education Study Program, Islamic University of Riau. This research is a type of quantitative descriptive research. The population and sample of this study were all students of the 5th semester of the 2020/2021 academic year, totaling 48 people. Collecting research data using documentation study techniques, and analyzed using descriptive analysis. The results showed that the critical thinking skills of Accounting Education students, on average, had good abilities. However, there are still some students who have a low critical thinking category. This is due to; 1) Some students are still formulating questions that are classified as CI and C2. 2) Students tend to answer questions briefly, without providing further explanation. 3) Students still use reasons that focus on the words of the book or take it directly from the internet without examining it first. Therefore, students must be encouraged to improve their abilities in critical thinking.